The effect of casein phosphopeptide-amorphous calcium phosphate on enamel surface rehardening. An in vitro study - (:unkn) unknown (My University, 2012)
AIM: Casein phosphopeptide stabilised amorphous calcium phosphate (CPP-ACP) has been shown to remineralise enamel subsurface lesions. The aim of this study was to determine the effect of a paste containing 10% CPP-ACP (Toothmousse; GC) on enamel surface microhardness in vitro. MATERIALS AND METHODS: Thirty enamel blocks (3x2 mm) were prepared for the study group from the buccal surface of extracted teeth. The microhardness of the enamel surface was determined for the specimens initially before artificial demineralisation. After demineralization the specimens were incubated in 10% CPP-ACP for 5 min. Artificial saliva was used as a remineralising solution for the control group. RESULTS: The mean baseline surface microhardness analyses of enamel blocks were 318.61±25.75 and 262.49±26.82. The data show that after demineralisation the mean microhardness decline in the experimental groups (247.05± 38.31 and 186.92± 63.77). The results showed that 10% CPP-ACP (281.79±26.32) was comparable to the control (252.27± 31.05) for remineralisation of enamel subsurface lesions in vitro. The highest surface microhardness recovery (%SMHR) was found for control, but the differences of % SMHR between 10% CPP-ACP and control was not statistically significant (p=0.805). CONCLUSION: From the results it can be concluded that CPP-ACP may have positive effects on enamel remineralisation.
Keywords: Humans; Hydrogen-Ion Concentration; Materials Testing; Dental Stress Analysis; Caseins; Cariostatic Agents; Tooth Demineralization; Tooth Remineralization; Cellulose; Hardness; Dental Enamel; Saliva, Artificial